Estimating fitness by competition assays between drug susceptible and resistant Mycobacterium tuberculosis of predominant lineages in Mumbai, India. - Purva Bhatter (Public Library of Science (PLoS), 2012)
Background Multi Drug Resistant Tuberculosis (MDR TB) is a threat to global tuberculosis control. A significant fitness cost has been associated with DR strains from specific lineages. Evaluation of the influence of the competing drug susceptible strains on fitness of drug resistant strains may have an important bearing on understanding the spread of MDR TB. The aim of this study was to evaluate the fitness of MDR TB strains, from a TB endemic region of western India: Mumbai, belonging to 3 predominant lineages namely CAS, Beijing and MANU in the presence of drug susceptible strains from the same lineages. Methodology Drug susceptible strains from a single lineage were mixed with drug resistant strain, bearing particular non synonymous mutation (rpoB D516V; inhA, A16G; katG, S315T1/T2) from the same or different lineages. Fitness of M.tuberculosis (M.tb) strains was evaluated using the difference in growth rates obtained by using the CFU assay system. Conclusion/significance While MANU were most fit amongst the drug susceptible strains of the 3 lineages, only Beijing MDR strains were found to grow in the presence of any of the competing drug susceptible strains. A disproportionate increase in Beijing MDR could be an alarm for an impending epidemic in this locale. In addition to particular non synonymous substitutions, the competing strains in an environment may impact the fitness of circulating drug resistant strains.